2020
DOI: 10.1038/s41408-020-00346-7
|View full text |Cite
|
Sign up to set email alerts
|

Infection during the first year in patients treated with CD19 CAR T cells for diffuse large B cell lymphoma

Abstract: CD19-targeted chimeric antigen receptor (CAR) T cell therapy is an effective treatment for diffuse large B cell lymphoma (DLBCL). In addition to cytokine release syndrome (CRS) and immune effector cell-associated neurotoxicity (ICANS), B cell aplasia and hypogammaglobulinemia are common toxicities predisposing these patients to infections. We analyzed 60 patients with DLBCL treated with FDA-approved CD19 CAR T cells and report the incidence, risk factors, and management of infections during the first year afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
227
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 187 publications
(293 citation statements)
references
References 28 publications
(53 reference statements)
13
227
5
1
Order By: Relevance
“…Treatments varied throughout the time period due to rapid iterative changes in clinical management algorithms. Documented secondary infections were uncommon, including in those patients who received IL-6-directed therapies, similar to CAR T recipients treated with tocilizumab for cytokine release syndrome (17,18). Interestingly, time from cellular therapy and many previously reported risk factors for disease severity were not significant in our analysis, though analyses were limited by the small number of events.…”
Section: Discussionmentioning
confidence: 67%
“…Treatments varied throughout the time period due to rapid iterative changes in clinical management algorithms. Documented secondary infections were uncommon, including in those patients who received IL-6-directed therapies, similar to CAR T recipients treated with tocilizumab for cytokine release syndrome (17,18). Interestingly, time from cellular therapy and many previously reported risk factors for disease severity were not significant in our analysis, though analyses were limited by the small number of events.…”
Section: Discussionmentioning
confidence: 67%
“…Seven published manuscripts and abstracts describing IFIs after CAR-T-cell therapy were identified at the time of this review [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Overall, IFIs after CAR-T-cell therapy are uncommon and have been reported in 1–15% of patients, with 0–10% and 0–7% of patients developing yeast and mold infections, respectively.…”
Section: Epidemiology Of Fungal Infections After Car-t-cell Therapmentioning
confidence: 99%
“…In one study which reported infections occurring >90 days after CAR-T-cell infusion, IFIs developed in 9% of patients and included two invasive mold infections, one yeast infection, and one endemic mycosis ( Coccidioides immitis infection) [ 10 ]. Six studies reported infection-related deaths, of which mortality attributable to IFIs ranged from 0 to 5% [ 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Epidemiology Of Fungal Infections After Car-t-cell Therapmentioning
confidence: 99%
See 1 more Smart Citation
“…Invasive mold infections were uncommon, ranging from 1 to 7% in CAR T-cell recipients [ 15 – 17 ]. In multivariate analyses, the use of systemic corticosteroids for the management of CRS or ICANS has emerged as a major risk factor of infection [ 18 ]. Certain inflammatory signatures – such as the “double peaks of IL-6” pattern observed in our patient – have been shown to confer an especially high risk of life-threatening infection [ 19 ].…”
Section: Discussionmentioning
confidence: 99%